(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
It is very important to use the detection technology of float glass thickness in glass production. In the process of detecting glass thickness on line, we adopt laser trigonometry displacement detection theory. Directing at detection system theory in the high-temperature state, the paper does a further analysis. The paper analyzes the theory and experimental results by using the CDD detection method. The research improves the precision and stability of the detection, increases the glass production quality and cuts down the energy consumption and production cost.